OP0270 Targeting IL-23 Can Attenuate Progression of Spinal Ankylosis in Ankylosing Spondylitis. (15th July 2016) - Jo, S.; Koo, B.S.; Koo, B.S.; Sung, I.-H.; Sung, I.-H.; Park, Y.-S.; Park, Y.-S.; Choi, C.-B.; Choi, C.-B.; Kim, T.-H.; Kim, T.-H.
Abstract : Background: IL-23 has been implicated in the development of ankylosing spondylitis (AS). The role of IL- 23 in AS pathogenesis has emerged as a therapeutic target. This study aimed to clarify that anti IL-23 blockade can prevent progression of bony ankylosing in AS patients. Objectives: We investigated endoplasmic reticulum (ER) stress and IL-23 cytokine could play a role in human bone-derived osteoblast cells and blocking it leads to regulation of bone-related genes and/or preventing bone ankylosis in AS. Methods: Primary human osteoblast cells were isolated from diced bones of facet joints which were taken from surgical operation of 8 AS patients and 8 healthy controls (HC). The tissues of facet joints in AS were stained and compared with those of HC. Osteoblast differentiation- and ER stress-related genes were determined by quantitative RT-PCR, immunoblotting, immunofluorescence, and immunohistochemistry. Osteoblast activity of all bones-derived osteoblast cells was confirmed by Alkaline Phosphatase activity (ALP) and Alizarin Red (ARS) staining. The ER stress by BIX, selective BIP inducer X, in the regulation of IL-23 expression and secretion was evaluated by quantitative RT-PCR and ELISA. Results: We found that elevated RUNX2, BIP, and IL-23 protein expressions were observed at osteoblast cells in human AS compared to HC. In addition, mRNA levels of bone differentiation (ALP, BMP2, COL1A, RUNX2, C/EBPβ, OPG, and OCN) and ER stress (BIP and CHOP)-related genes were highly expressed in human AS. In particular, IL-23 and RUNX2 expressions were significantly increased in AS. BIX-mediated ER stress stimulated induction of osteoblast activity and IL-23 secretion via modulating RUNX2 and C/EBPβ genes. Intriguingly, RUNX2 Knockdown by shRNA impeded ER stress-induced effects. Moreover, osteoblast activity and RUNX2 expression in AS were significantly reduced by IL-23 blockers, but not TNFα blockers. Conclusions: This is the first report to show that ER stress, osteoblastic activity, and IL-23 expression in AS were increased compared to HC, suggesting that sustained ER stress induces osteoblast activity and IL-23 expression. Notably, these effects in AS were reduced by IL-23 blockade. Taken together, our results supported that blocking IL-23 may represent a promising therapeutic target to assist and prevent bony progression in AS. Disclosure of Interest: None declared